Evaluation of oleoresin-based compounds as additives to diesel fuels (2020)
ABSTRACT: Despite the marked reduction in proven reserves of fossil fuels and their contribution to global warming, it is expected that diesel engines will continue to play a key role in road transportation worldwide : on the one hand, diesel engines present high power-output, fuel and thermal efficiency, and durability; and, on the other, new technologies still need to overcome technical limitations and reach the stage of economic viability. Furthermore, as the road to cleaner and environmentally-friendly transportation would include biofuels, sustainability issues should be considered, such as the feedstock used in the production of the biofuel. In particular, conifer trees, which are encountered in many places on earth and may growth in otherwise barren soils, produce pine oleoresin by bleeding; pine oleoresin can be also obtained as a byproduct of Kraft process in the pulp industry. Turpentine oil and the non-volatile rosin or colophony are then obtained by distillation of oleoresin. Turpentine has been tested as additive (i.e., below 1%) in several fuel formulations and directly as component (i.e., up to 40%) in diesel fuels, and its transformation, e.g., hydrogenation (to remove unsaturation) and oxyfunctionalization, has been proposed. Prior transformations are required to use of rosin as fuel, however, to break its heavy and complex molecules into smaller hydrocarbons. In this work, the potential of oleoresin-oxygenated molecules as components or additives of diesel fuel was evaluated. Firstly, the combustion of five molecules which can be obtained from oleoresin by oxyfunctionalization (i.e., nopol, terpineol — with α-terpineol as the main isomer, myrtenol, borneol, and abietic acid methyl ester — AAME) was studied to assess their influence on emissions of the main pollutants (carbon monoxide — CO, unburned hydrocarbons — UHC, and nitrogen oxides — NOx) and flame characteristics (i.e., temperature and height) in non-premixed co-flow laminar flames of n-heptane + oleoresin derivative blends. CO and UHC emission were reduced and the flame temperature was increased (leading to an increase in NOx emissions) in the blends with alcohols, which suggests an improvement in the combustion. Nopol stands out between the alcohols probably due to the longest sidechain where the hydroxyl group is attached in. Conversely, AAME, which, although soluble in n-heptane at low content, is solid at ambient conditions, showed a deterioration in the combustion. The Prins condensation reaction was then performed to transform β-pinene from turpentine into nopol without previous separation (the molecule with best performance in the combustion tests), with high conversion and high selectivity (>99%). The reaction was scaled-up to 10 L with minor impact on the performance. Furthermore, the properties of blends of the oxyfunctionalized turpentine in diesel up to 20 % vol. are within the limits established by European Standard EN 590:2013 (diesel fuel with high quality). In addition, this blend was used as fuel in a Euro 6 direct injection engine to evaluate the influence of oxyturpentine on performance and emissions. A reduction in particulate number, particulate matter and nitrogen oxides, and an increase in carbon monoxide and hydrocarbon emissions (as it has been reported for oxygenated fuels such as alcohols) was observed. All emissions were under the limits established by the NEDC protocol (a valid protocol for vehicle testing currently in Colombia and other American, Asian and African countries), suggesting a high potential of the oxygenated turpentine as component of diesel fuel.